Analisis Peran Negara Di Bidang Ekonomi Dalam Prespektif Sistem Kapitalisme, Sosialisme, Dan Ekonomi Islam - Muhammad Kambali (JES (Jurnal Ekonomi Syariah), 2016)
The economic crisis that convolved the world economy a few years ago is the result of a series of government policies in the economic field. Starting from the Subprime Mortgage in America, the crisis eventually spreads across all sectors of the economy. As analysts say that the explosion of the current economic crisis is caused by the trend of low interest rates that are applied by the Fed. The trend of low interest rates will give rise to expectation of market to future economic situation. It is characterized by the overflow of capital expansion in all sectors, especially in property sector. Today, along with the growing mobility of capital from one country to another as part of unavoidable economic liberalization, mobility of capital, on the one hand, has spawned some of the imbalances in the life of a State. The powerlessness can not be separated from economic ideology and system on state role in the economy. Capitalism with its laissez faire brings the concept of state minimal role in the economy. In the empirical facts, it is broken by the crisis situation in 1930 and today's financial crisis. Socialism tends to carry the central role of the State in the economy through the centralistic planning system. The fall of the Soviet Union in the 1980s brought the world to a choice whether reconstructing capitalism or socialism as Fukuyama and Gidden said. On the other hand, as the new system, the economic system of Islam brings the concept of the role of the State in the economy on the basis of universal values of Islam, such as justice in the economy which is reflected in the mechanism of the prohibition of riba (usury), just income distribution and redistribution of income through zakat and social security. This article is an exposure of the State's role in the economy which is studied through the perspective of today’s economic system. The systems are capitalism, socialism, and Islam. The article not only explores conceptual framework, but also also contains an empirical framework mapping and how the conceptual framework is operated. At the end, from the two mapping (conceptual and empirical), author draws a reflection of how the State should play a role in the economic field. Keywords: Capitalism, Socialism, Islam, Economic Role of State